TINGKAT KEMATANGAN GURU DAN SISWA PENDIDIKAN VOKASIONAL DALAM MENERAPKAN KETERAMPILAN ABAD 21 - Juliandarini (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2022)
Until now, the maturity level of teachers and students in vocational education in applying 21st century skills in learning is still a prolonged polemic. This study aims to: (1) analyze the maturity level of teachers and students in applying 21st century skills; (2) analyze the difference in the maturity level of 21st century skills between teachers and students in implementing vocational learning. The research uses an exploratory descriptive method with a quantitative approach adopting the Hoy and Adam design. This study involved 598 samples which were divided into teacher and student subjects. Collecting data using a closed questionnaire technique with a 4-point Likert scale. Data were analyzed descriptively quantitatively to describe the percentage of maturity level and independent sample t-test to determine the difference in maturity between teachers and students. The results showed: (1) all 21st century skills consisting of problem solving, critical thinking, creativity, collaboration, communication, and digital literacy were at a low level of maturity; (2) the difference in the level of maturity experienced by teachers and students is quite significant in all competencies. Currently, 21st century skills in managing and following learning in vocational education must be strengthened again. Various training and mentoring for teachers and students should also be improved.